2014
DOI: 10.5152/eurjrheumatol.2014.140049
|View full text |Cite
|
Sign up to set email alerts
|

A successful treatment of juvenile idiopathic arthritis with rituximab: A report of two cases

Abstract: Juvenile idiopathic arthritis (JIA) is defined as arthritis of unknown cause that starts before 16 years of age and lasts at least 6 weeks. It is the most common chronic inflammatory disease in childhood and often persists through adulthood and can lead to severe disability. Biologics are an important therapeutic option for treating patients with JIA. The efficiency of rituximab has not been proven for this indication. Its use has rarely been reported in the literature. We report two new cases of severe and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In terms of oligo-JIA and RF- poly-JIA, especially those that have ANA, there is considerable evidence that rituximab treatment may be a worthwhile treatment option. Several case studies have demonstrated that rituximab therapy can produce sustained clinical improvement in patients with refractory disease (98100). Currently, rituximab is often only considered following the failure of first-line treatments such as TNF inhibitors and methotrexate in both pediatric and adult disease.…”
Section: B Cell Targeted-therapies In Pediatric Rheumatic Diseasementioning
confidence: 99%
“…In terms of oligo-JIA and RF- poly-JIA, especially those that have ANA, there is considerable evidence that rituximab treatment may be a worthwhile treatment option. Several case studies have demonstrated that rituximab therapy can produce sustained clinical improvement in patients with refractory disease (98100). Currently, rituximab is often only considered following the failure of first-line treatments such as TNF inhibitors and methotrexate in both pediatric and adult disease.…”
Section: B Cell Targeted-therapies In Pediatric Rheumatic Diseasementioning
confidence: 99%
“…In our patient, a variety of steroid-sparing agents with different mechanisms of action have been employed with limited or no clinical success. Some of these agents were used in line with current treatment recommendations, but many were used based on anecdotal reports [24][25][26][27][28]. Finally, due to signs of systemic inflammation characterized by increased inflammatory markers (CRP and ESR) and cytokines (IL-6 and TNF-alfa), which is indicative for the activation of JAK/STAT pathway, treatment with tofacitinib, a first generation JAK inhibitor, was initiated with a good clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Biologics are genetically engineered drugs that work by selectively blocking the effects of cytokines. [11][12][13][14][15][16][17][18][19] Multiple biologics have been approved for the treatment of rheumatoid arthritis (RA) in adult patients. 22,23 The use of biologics in pediatric population are still limited in Indonesia.…”
Section: Lapsusmentioning
confidence: 99%